Pengaruh Penerapan Akad Isthisna Terhadap Minat Beli Masyarakat Di Perumahan Nakhil Garden Pawarengan Cikampek Barat - Dian Rosdiana; Ahmad Ali Sopian; Jalaludin Jalaludin (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2021)
The need for housing is a basic need after the need for clothing and food. Housing Nakhil Garden Pawarengan Cikampek is one of the sharia property developers that provides ready-to-build residential products, using a non-bank sharia system in running their business, namely using an isthisna contract or advance reservation without any touch of usury. The purpose of this study was to determine the effect of the application of the Istishna contract on people's buying interest in the Nakhil Garden Pawarengan Cikampek housing, and to determine how much influence the application of the Istishna contract had on the public's interest in buying housing at Nakhil Garden Pawarengan Cikampek. This study uses quantitative methods, data collection is done by means of observation, interviews, distributing questionnaires and documentation respondent data. The population in this study are consumers who buy and are interested in buying housing with a sample of 40 people. The sampling technique is probability sampling using simple random sampling. The type of data used is primary data with a questionnaire data collection method. Then the analysis technique using simple linear regression data analysis. The results of this study indicate that the isthisna contract applied by Nakhil Garden housing has no effect on people's buying interest, this can be seen from the results of the regression test, namely the value of the coefficient of determination (R Square) generated is 0.187 from the correlation / relationship value ( R) of 0.432. so that it can be interpreted that the application of the Istishna contract has an influence on buying interest in Nakhil Garden Pawarengan housing by 18.7%, the remaining 81.3% is influenced by other factors not examined in this study